2021
DOI: 10.1038/s41598-021-82338-6
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment correlation in financial news networks and associated market movements

Abstract: In an increasingly connected global market, news sentiment towards one company may not only indicate its own market performance, but can also be associated with a broader movement on the sentiment and performance of other companies from the same or even different sectors. In this paper, we apply NLP techniques to understand news sentiment of 87 companies among the most reported on Reuters for a period of 7 years. We investigate the propagation of such sentiment in company networks and evaluate the associated m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…A correlation between market sentiments and financial news was investigated by other researchers using data from October 2006 to November 2013 (Wan et al 2021 ). The results showed that the Technology space had highly positive sentiments and banks were negative due to the 2008 crash.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between market sentiments and financial news was investigated by other researchers using data from October 2006 to November 2013 (Wan et al 2021 ). The results showed that the Technology space had highly positive sentiments and banks were negative due to the 2008 crash.…”
Section: Discussionmentioning
confidence: 99%
“…The news sentiment could indicate in advance the evolution of the market value of public companies. Indeed, Audrino et al (2020) find that sentiment variables are able to improve volatility forecasts significantly, whereas Wan et al (2021) demonstrate that there exists a weak but statistically significant association between strong media sentiment and abnormal market return as well as volatility.…”
Section: The Influence Of Financial Newsmentioning
confidence: 98%
“…In the same context, Cerchiello and Nicola (2018) use news archives from Reuters and Bloomberg and investigate causal effects in the diffusion of the news by means of Granger-causality tests and show that both the temporal dynamics and the spatial differentiation matter in the news contagion. Also, Wan et al (2021) investigate the propagation of news sentiment in company networks and evaluate the associated market movements in terms of stock price and volatility, arguing that strong media sentiment towards one company may be a sign of significant change in media sentiment towards related companies.…”
Section: Connecting Contagion and Systemic Riskmentioning
confidence: 99%
“…In fact, both EMH and modern behavioral finance believe that the volatility of the stock market comes from the release, dissemination, and utilization of information, although they hold different views on how information shapes stock movements [1]. With more and more evidence emerging that stock prices cannot incorporate new information instantly, it is now widely accepted that news reports, whether they contain new information or only capture stale information, have significant effects on stock returns and volatility, and can help predict stock movement [27][28][29][30]. Tetlock [31] found that media tone has an impact on stock returns.…”
Section: 1mentioning
confidence: 99%